2021
DOI: 10.1289/ehp6993
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Tox21 Chemical Collection for Acetylcholinesterase Inhibition

Abstract: Background: Inhibition of acetylcholinesterase (AChE), a biomarker of organophosphorous and carbamate exposure in environmental and occupational human health, has been commonly used to identify potential safety liabilities. So far, many environmental chemicals, including drug candidates, food additives, and industrial chemicals, have not been thoroughly evaluated for their inhibitory effects on AChE activity. AChE inhibitors can have therapeutic applications (e.g., tacrine and donepezil) or neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…We postulate that this reduction in bioactivity is most likely due to non-specific protein binding because similar results were observed with heat-attenuated microsomes (data not shown). Similar findings were also observed in our previously conducted screening for acetylcholinesterase inhibitors (Li et al 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We postulate that this reduction in bioactivity is most likely due to non-specific protein binding because similar results were observed with heat-attenuated microsomes (data not shown). Similar findings were also observed in our previously conducted screening for acetylcholinesterase inhibitors (Li et al 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The enriched clusters mainly contain organophosphates, organothiophosphates, and organochlorines, chemical classes that are often used as pesticides. Results from an earlier study looking at inhibition of AChE activity in a cell-free system (Li et al 2021 ) confirmed the need for many organophosphates, such as chlorpyrifos, to undergo biotransformation for activity. Enhanced activity following biotransformation is not limited to pesticides, but extends to a number of other environmental compounds such as polycyclic aromatic hydrocarbons (Sen et al 2013 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The Toxicology in the 21st Century (Tox21) program is a US federal research collaboration between the US Environmental Protection Agency, the National Toxicology Program, the National Center for Advancing Translational Sciences, and the Food and Drug Administration that aims to develop toxicity assessment methods for commercial chemicals, pesticides, food additives/contaminants, and medical products using quantitative high-throughput screening [ 5 , 6 , 7 ]. The Tox21 10K library consists of approximately 10,000 (10K) chemicals, including nearly 100 million data points obtained by in vitro quantitative high-throughput screening, indicating the toxicological risk of chemical compounds obtained using an in silico approach [ 8 , 9 ]. Using Tox21 data, the quantitative structure–activity relationship (QSAR) competition organized by Merck—referred to as the Tox21 Data Challenge 2014—demonstrated high-performance prediction modeling using machine learning (ML) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently implemented in vitro assays for measuring acetylcholinesterase (AChE) inhibition, a mechanism of toxicity, into Tox21 and published our study in Environmental Health Perspectives [4] . Chemicals that inhibit AChE activity block the metabolism of acetylcholine [5] , leading to overstimulation of cholinergic receptors and toxicologi- cal effects (e.g., salivation, lacrimation, urination, diaphoresis, gastrointestinal distress, emesis, and paralysis) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%